Economic volatility and sovereign yields’ determinants : a time-varying approach - Afonso, António (2016)
Using quarterly data for 10 Euro Area countries we assess the determinants of government bond yield spreads; compute bivariate time-varying coefficient models of each determinant; and use these estimates to explain economic volatility. We find that better fiscal positions or higher than expected growth prospects reduce the yield spreads, while increases in the VIX, and bid ask, debt-to-GDP ratio or real effective exchange rate increase the spreads. Moreover, the responsiveness of the yield spread determinants increased in the run-up to the Global Financial Crisis. Finally, for the case of the budget balance and real GDP growth (bid ask spread, debt-to-GDP ratio, real effect exchange rate and VIX), the larger (higher) in absolute value the corresponding spread’s responsiveness, the lower (higher) is economic volatility.